Efeito da técnica de cimentação na resistência à fratura de coroas cerâmicas reforçadas por silicato de lítio - Garcia, André Vivan (2019)
The aim of this study was to evaluate the effect of the luting technique with preheated composite resins on the fracture strength of CAD / CAM lithium silicate reinforced glassceramics. Thirty crowns were fabricated by milling partially crystallized blocks (Suprinity - Vita Zanfabrik) from a master model with preparation for total crown referring to a superior molar. The master model was duplicated with addition silicone and thirty replicates of the epoxy resin preparation were made. After milling, the crowns went through a process of final crystallization, finishing and vitrification. The specimens were distributed in three groups (n = 10), according to the material used for cementation: Resin Cement (AllCem - FGM), Composite resin with lower elastic modulus (Herculite Classic - Kerr) and composite resin with higher elastic modulus (Filtek Z350 XT - 3M). All adhesive procedures were performed according to the manufacturer’s recommendations. The test groups were cemented with composite resins preheated to 68°C. The samples were stored in distilled water at 37°C for 24 hours. After this period, they were submitted to thermocycling (10,000 cycles of 30 seconds). For the fracture test, a gradual axial compressive load was applied to the center of the occlusal face of the crown using a universal testing machine (DL 2000 - EMIC) and a 500 kg load cell with a hemi spherical piston with 6 mm diameter at a loading rate of 0.5 mm / min until fracture of the specimen occurs. All samples were evaluated to classify the type of failure after the mechanical test. The fracture resistance data were subjected to statistical analysis (one-way ANOVA - p <0.05%). According to the results, no significant difference was observed among groups. Class II failure type was the most frequent. It was concluded that the heat treatment applied in the composite resins did not interfere in the fracture strength of reinforced lithium silicate glass-ceramics produced by CAD / CAM.